2005
DOI: 10.2298/psi0503311s
|View full text |Cite
|
Sign up to set email alerts
|

Problems of the defining the dimensions of the Gray's reinforcement sensitivity theory

Abstract: Jeffrey Gray has modified Eysenck's system by rotating the dimensions of extraversion and neuroticism by 45 degrees, which resulted in two new dimensions: impulsivity (behavioral approach system) and anxiety (behavioral inhibition system). The main purpose of this study was to examine psychometric properties of the BIS/BAS scale, inventory for assessment of dimensions included in Gray's theory, in order to, also, test the foundation of the Gray's constructs themselves. 476 participants were included, age 17 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The authors of the inventory have declared it free to use for noncommercial purposes. The Serbian/Croatian version of the inventory, which was used in this study is the version which was previously used in a number of studies in Serbia [11][12][13][14] . Stojanović 15 conducted a study on a sample of 304 participants from Serbia, which demonstrated convergence of BFI measures to analogues personality trait measures obtained by using NEO Personality Inventory -Revised (NEO PI-R).…”
Section: Methodsmentioning
confidence: 99%
“…The authors of the inventory have declared it free to use for noncommercial purposes. The Serbian/Croatian version of the inventory, which was used in this study is the version which was previously used in a number of studies in Serbia [11][12][13][14] . Stojanović 15 conducted a study on a sample of 304 participants from Serbia, which demonstrated convergence of BFI measures to analogues personality trait measures obtained by using NEO Personality Inventory -Revised (NEO PI-R).…”
Section: Methodsmentioning
confidence: 99%